Transcriptome analysis of interactions between silkworm and cytoplasmic polyhedrosis virus - Jiang, Liang (Sci Rep, 2016)
Bombyx mori cytoplasmic polyhedrosis virus (BmCPV) specifically infects silkworm midgut (MG) and multiplication occurs mainly in posterior midgut (PM). In this study, MG and fat body (FB) were extracted at 0, 3, 24, and 72 h after BmCPV infection. The total sequence reads of each sample were more than 1510000, and the mapping ratio exceeded 95.3%. Upregulated transcripts increased in MG during the infection process. Gene ontology (GO) categories showed that antioxidants were all upregulated in FB but not in MG. BGI001299, BGI014434, BGI012068, and BGI009201 were MG-specific genes with transmembrane transport function, the expression of which were induced by BmCPV. BGI001299, BGI014434, and BGI012068 expressed in entire MG and may be involved in BmCPV invasion. BGI009201 expressed only in PM and may be necessary for BmCPV proliferation. BmPGRP-S2 and BGI012452 (a putative serine protease) were induced by BmCPV and may be involved in immune defense against BmCPV. The expression level of BmCPV S1, S2, S3, S6, and S7 was high and there was no expression of S9 in MG 72 h, implying that the expression time of structural protein coding genes is earlier. These results provide insights into the mechanism of BmCPV infection and host defense.